PENGARUH MIKORIZA DAN JARAK TANAM TERHADAP HASIL TANAMAN JAGUNG MANIS (Zea mays var. saccharata Sturt) - Wisnu Utomo; Murti Astiningrum; Yulia Eko Susilowati (JURNAL VIGOR, 2017)
The research about effort to increase the yield of sweet corn (Zea mays var. saccharata Strurt.) using mikoriza doses and planting distance was conducted in August until November 2016. Location in forestry and agriculture institute axperimental Dlimas, Tegalrejo, Magelang. The altitude 478 m using latosol soil with pH 6,8. A research tipe (3X3) factorial experiment arrangged in randomized completed, block design repeated three times. The first factor was mikoriza dose of 0, 30 and 60 g/plant. The second factor was planting distance of 70 cm X 20 cm, 70 cm X 30 cm and 70 cm X 40 cm. The result of the research showed that mikoriza dose of 30 g/plant can increase the highly on number of leaves, weight of cob with husks per plant, weight of cob without husks per plant, cob lenght, composition of sugar and number of lines. Planting distance of 70 cm X 20 cm gived the highest plant height. While planting space of 70 cm X 40 cm gived the highest of leaves number, weight of cob with husks per plant, weight of cob without husks per plant, cob lenght, composition of sugar and the number of lines. Increasing mikoriza dose and planting distance different on the number of leaves.